DIFFERENT FOCI OF FOREIGN POLICY ANALYSIS IN „FOREIGN AFFAIRS”: RUSSIAN POLICY TOWARDS THE WEST IN 1999͵2013 - Walewicz, Piotr (Torun International Studies, 2018)
Articles in Foreign Affairs have always been an informative collection of opinions, which allowed understanding how the U.S., and especially its intellectuals that comment on international relations, perceive other countries and their foreign policies. Then when an international crisis comes, such as the one in Ukraine in 2014 and the subsequent annexation of Crimea, one wonders if the Western analysts might have predicted such outcome. The article analyzes more than three dozen Foreign Affairs publications from 1999 to 2013 and concludes that the authors held rather close-minded views when it comes to foreign policy analysis. They did not present a holistic standpoint, but tried to answer all questions with only a limited number of tools and foci. It is also concluded that combining the realist, liberal internationalist and constructivist attitudes would have allowed for a more comprehensive analysis of the process of creation of Russian foreign policy.